Coworker Reports about Unprofessional Behavior in Plastic Surgery. Issue 4 (9th December 2022) - White-Dzuro, Colin G.; Glassman, Gabriella E.; Patrinely, James R.; Walker, Sallie; Stratton, Shannon; Domenico, Henry J.; Galloway, Mitchell; Pichert, James W.; Perdikis, Galen; Cooper, William O.
Abstract : Background: Patient reports of unprofessional conduct by surgeons have been linked to postprocedure complications and increased risk for malpractice claims. Coworkers are also positioned to observe and report unprofessional behaviors, including concerns related to delivery of competent medical care, clear and respectful communication, integrity, and responsibility. This study compared rates of coworker concerns between plastic surgeons and other physicians (other surgical specialists and nonsurgeons), and characterized whether plastic surgery subspecialties differed in their rates of complaints. Methods: Coworker concern data from January 1, 2014, to December 31, 2019, were retrieved from the Vanderbilt Center for Patient and Professional Advocacy's Coworker Observation Reporting System database. Specialty was classified as plastic surgery, non–plastic surgical, and nonsurgical. The plastic surgery cohort was further characterized by sex, medical school graduation year, predominant practice type (reconstructive only, aesthetic only, or hybrid), and postresidency training (ie, completion of a fellowship). Results: The study cohort included 34, 170 physicians (302 plastic surgeons, 7593 non–plastic surgeons, and 26, 275 nonsurgeons). A greater proportion of plastic surgeons (13.6%) had one or more coworker concerns compared with nonsurgeons (10.8%) and non–plastic surgeons (6.1%) ( P < 0.001). The most prevalent concern category reported for plastic surgeons was clear and respectful communication. Among plastic surgeons who had no concerns versus those who had at least one concern, there was no significant difference when comparing sex, medical school graduation year, predominant practice type, or postresidency training. Conclusions: Plastic surgeons in this cohort study received more coworker reports than other surgeons and nonsurgical physicians. These data may be used by institutions to identify plastic surgeons at risk for preventable postprocedure complications and intervene with peer feedback intended to promote self-regulation.